2018
DOI: 10.1007/s11095-018-2526-y
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan Alters the Disposition of Morphine Via Inhibition of Organic Cation Transporter 1 (OCT1) and 2 (OCT2)

Abstract: Purpose The organic cation transporters (OCTs) and multi-drug and toxin extrusions (MATEs) together are regarded as an organic cation transport system critical to the disposition and response of many organic cationic drugs. Patient response to the analgesic morphine, a characterized substrate for human OCT1, is highly variable. This study was aimed to examine whether there is any organic cation transporter-mediated drug and drug interaction (DDI) between morphine and commonly co-administrated drugs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…The IC 50 for OCT1 was 608 mM and for OCT2 was 0.14 mM. As reported previously (Kido et al, 2011;Zhu et al, 2018), potent OCT inhibition was observed by imipramine and verapamil; IC 50 values for OCT1 were 0.67 and 10.1 mM, respectively, and were 0.14 and 0.11 mM for OCT2 (data not shown). After accounting for the effect of all three inhibitors in VC cells, the ratios of uptake in OCT1 cells with/without inhibitor over VC cells with/without inhibitor are consistent with each inhibitor, and represent the effect of each inhibitor specifically on OCT1-mediated uptake, shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…The IC 50 for OCT1 was 608 mM and for OCT2 was 0.14 mM. As reported previously (Kido et al, 2011;Zhu et al, 2018), potent OCT inhibition was observed by imipramine and verapamil; IC 50 values for OCT1 were 0.67 and 10.1 mM, respectively, and were 0.14 and 0.11 mM for OCT2 (data not shown). After accounting for the effect of all three inhibitors in VC cells, the ratios of uptake in OCT1 cells with/without inhibitor over VC cells with/without inhibitor are consistent with each inhibitor, and represent the effect of each inhibitor specifically on OCT1-mediated uptake, shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, inclusion of these transporters could be important for modeling oral dosing data, which was not the focus in this study. In addition, studies in HEK293‐OCT2 cells suggest that morphine is a substrate of the renal transporter OCT2 48 . However, the influence of OCT2 on morphine disposition is expected to be low because only < 10% of morphine is recovered unchanged in urine 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in HEK293-OCT2 cells suggest that morphine is a substrate of the renal transporter OCT2. 48 However, the influence of OCT2 on morphine disposition is expected to be low because only < 10% of morphine is recovered unchanged in urine. 20,21 Although M3G is not a substrate of OATP2B1, 48 data from uptake studies in hepatocytes suggest that OATP1B transporters are involved in M3G uptake into the liver.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…With the increased risk of opioid overdose and adverse events in people with CKD 12 transporters (OCTs) in the hepatic uptake is recognized (36,37). The present study utilized a VPT-MPS to evaluate the kidney secretion of morphine and M6G and to predict kidney clearance of these compounds in humans.…”
Section: Discussionmentioning
confidence: 99%